Factors Influencing Small Business Start-Ups in Kathmandu Valley - Bohara, Aakriti (Nepalese Journal of Business, 2024)
This study examines the factors influencing small business start-ups in Kathmandu Valley. Performance of small business is the dependent variable. The selected independent variables are financial resources, socio-cultural factor, entrepreneurial skills, country business law, and competition. The primary source of data is used to assess the opinion of respondents regarding financial resources, socio-cultural factor, entrepreneurial skills, country business law, and competition. The study is based on 125 respondents from Kathmandu Valley. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of factors influencing small business start-ups in Kathmandu Valley. The result shows that the financial resources are positively correlated to business performance. It indicates that better financial resources lead to increase in business performance of small business start-ups. Likewise, socio-cultural factor is positively correlated to business performance. It indicates that socio-cultural factor leads to increase in business performance of small business start-ups. Similarly, entrepreneurial skills are positively correlated to business performance. It indicates that entrepreneurial skills lead to increase in business performance of small business start-ups. Further, country’s business laws are also positively correlated to the business performance. It indicates that supportive country’s business laws lead to increase in business performance of small business start ups. Likewise, competition is positively correlated to business performance. It implies that healthy competition leads to increase in business performance of small business start-ups.